Risk Factors and Oncologic Outcomes for Clinical T1 Renal Cell Carcinoma Upstaging to Pathological T3a and The Construction of Predictive Model: A Retrospective Study: Predictors of upstaging to pT3a in renal carcinoma - Wang, Huadong; Wang, Keruo; Liu, Chuanfeng; Wang, Guixin; Liu, Yaru; Li, Gang (Urology Journal, 2023)
Purpose: The study is intended to identify the independent predictors of clinical T1 (cT1) renal cell carcinoma upstaging to pathological T3a (pT3a) and construct the predictive nomogram model. Methods: The data of cT1 renal cell carcinoma was collected from patients who were treated in the Second Hospital of Tianjin Medical University from January 2010 to December 2016. Mann–Whitney U and chi-square tests were performed to analyze continuous and categorical variables respectively. Univariate and multivariate logistic regression were used to identify the predictors of upstaging. Kaplan-Meier method, log-rank test and Cox regression were performed to analyze survival materials. Results: Among 1,376 cT1 renal cell carcinoma patients, 75 patients were observed upstaging to pT3a, accounting for 5.5%. There were 6 potential predictors of upstaging, i.e age, clinical symptom, tumor size, Fuhrman grade, tumor necrosis and tumor edge regularity. The 5-year recurrence free survival probabilities of upstaging and non-upstaging patients were 73.3% and 91.1%, respectively and upstaging was an independent predictor of recurrence free survival. Two predictive nomograms were constructed and the C-index of them were 0.842 and 0.806, and the calibration curve and decision curve analysis showed highly clinical accuracy of the nomograms. Conclusion: Two nomogram models were built to predict the probability of cT1 renal cell carcinoma upstaging to pT3a with highly accuracy and specificity. Upstaging was an independent risk factor of recurrence free survival for cT1 renal cell carcinoma patients.